Comparison of Bupivacaine, Ropivacaine, and Levobupivacaine in an Equal Dose and Concentration for Sympathetic Block in Dogs. Issue 5 (1st August 2010) - Hashimoto, Tomoki; Iwasaki, Tadaomi; Takahashi, Yoshiyuki; Kimura, Yoshiyuki; Nagao, Masaru; Yamaguchi, Shigeki; Hamaguchi, Shinsuke; Kitajima, Toshimitsu
Abstract : Background and Objectives: The aim of this study was to compare the potency of bupivacaine, ropivacaine, and levobupivacaine in an equal dose and concentration for sympathetic block. Methods: We measured mean arterial pressure, heart rate (HR), and right and left brachial artery blood flow (BABF) before and after cervicothoracic sympathetic block in 24 dogs. The experimental protocol was designed as follows: (1) left cervicothoracic sympathetic block with 1.0 mL of 0.25% bupivacaine (n = 8), (2) left cervicothoracic sympathetic block with 1.0 mL of 0.25% ropivacaine (n = 8), and (3) left cervicothoracic sympathetic block with 1.0 mL of 0.25% levobupivacaine (n = 8). Results: Mean arterial pressure and heart rate did not change significantly throughout the study in either group. Left cervicothoracic sympathetic block with 0.25% bupivacaine increased left BABF significantly from 5 to 100 mins after the block (baseline, 100%; peak at 20 mins after the block, 218% ± 48%; P < 0.01). Left cervicothoracic sympathetic block with 0.25% ropivacaine increased left BABF significantly from 5 to 100 mins after the block (baseline, 100%; peak at 10 mins after the block, 254 ± 38%; P < 0.01). Left cervicothoracic sympathetic block with 0.25% levobupivacaine increased left BABF significantly from 5 to 80 mins after the block (baseline, 100%; peak at 20 mins after the block, 183% ± 38%; P < 0.01). Conclusions: Ropivacaine may induce a greater increase in vasodilation than bupivacaine and levobupivacaine at the same dose and concentration for sympathetic block in dogs.